Survey Based Risk Assessment for Advancing the Safe Industrial Railway Transportation - Nwokocha, Geraldine Chika (International Journal of Membrane Science and Technology, 2023)
The linkage between producers of raw materials and final consumption goods producers is an end-to-end procedure involving transport machines, equipment, and technological influence. After producing final consumption goods, they are not left idle in the company; instead, they are transported to various market utilization parts. To familiarize and evaluate risks involved in the transportation system between suppliers of raw materials to producers of goods than to final consumers of such goods, Railway transport seemed more secure and confidential. We hypothesized the value of management of possible collision risks. The outcomes herein validate this hypothesis bearing in mind possible shipping of hazardous or perishable goods for quite a more extended period. A closer consideration of the new Train Control System (TCS) in train controls can be a better idea for new market entrants.